Electrochemistry in light water reactors : reference electrodes, measurement, corrosion and tribocorrosion issues - Bosch, R.-W. (Rik-Wouter); Feron, D.; Celis, Jean-Pierre (Woodhead Publishing in materials., 2007)
There has long been a need for effective methods of measuring corrosion within light water nuclear reactors. This important volume discusses key issues surrounding the development of high temperature reference electrodes and other electrochemical techniques. The book is divided into three parts with part one reviewing the latest developments in the use of reference electrode technology in both pressurised water and boiling water reactors. Parts two and three cover different types of corrosion and tribocorrosion and ways they can be measured using such techniques as electrochemical impedance spectroscopy. Topics covered across the book include in-pile testing, modelling techniques and the tribocorrosion behaviour of stainless steel under reactor conditions. Electrochemistry in light water reactors is a valuable reference for all those concerned with corrosion problems in this key technology for the power industry. Discusses key issues surrounding the development of high temperature reference eletrodesA valuable reference for all concerned with corrosion problems in this key technology.